Association of Cardiovascular Risk Factors between Adolescents and Their Parents Is Mitigated by Parental Physical Activity—A Cross-Sectional Study - Tebar, William R. [UNESP]; Ferrari, Gerson; Mota, Jorge; Antunes, Ewerton P. [UNESP]; Aguilar, Beatriz A. S. [UNESP]; Brazo-Sayavera, Javier; Christofaro, Diego G. D. [UNESP] (MDPI, 2022)
Introduction: It is hypothesized that children’s habits can be modulated by their parent’s lifestyle. However, it is still not established whether the relationship between cardiovascular risk factors (CVRF) in adolescents and their parents could be attenuated by parental physical activity levels. Objective: This study aimed to analyze the relationship of CVRF between adolescents and their parents according to parental physical activity level. Methods: A school-based sample of 1231 adolescents, 1202 mothers and 871 fathers were included (n = 3304). The CVRF assessed were overweight, hypertension, smoking and alcohol consumption. The parental physical activity level was assessed using a validated questionnaire, being classified into physically active and inactive parents. The statistical analysis considered all parents and stratification by physical activity level. Results: The prevalence of CVRF was higher in fathers than in mothers (70.6% vs. 54.9% for overweight, 23.3% vs. 19.7% for hypertension, 17.9% vs. 12.4% for smoking and 60.4% vs. 28.5% for alcohol consumption). Adolescents with active mothers showed lower prevalence of overweight (13.9% vs. 19.6%), while adolescents with active fathers showed higher prevalence of alcohol consumption (23.5% vs. 16.9%). The CVRF of both fathers and mothers were positively associated with CVRF of adolescents. However, the association of CVRF between adolescents and their parents was mitigated among active parents, while all the CVRF remained associated in physically inactive parents. Conclusion: The parental physical activity level seems to mitigate the association of CVRF between adolescents and their parents. The promotion of an active lifestyle at the family level can contribute to reduce CVRF among adolescents.
Keywords: exercise; hypertension; overweight; parent–child; substance use